Association of amyloidosis cutis dyschromica and familial Mediterranean fever - Asli Akin Belli; Asude Kara; Yelda Dere; Nevin Yilmaz (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Amyloidosis cutis dyschromica is a rare type of primary cutaneous amyloidosis characterized by reticulate hyper-pigmentation with discrete hypopigmented macules. Up to date, about 50 cases of amyloidosis cutis dyschromica have been reported and the majority are familial cases of Asian ethnicity. Various diseases, particularly autoimmune diseases such as systemic sclerosis and systemic lupus erythematosus, have been associated with amyloidosis cutis dyschromica. Herein, we report a case of amyloidosis cutis dyschromica accompanying familial Mediterranean fever with a delayed diagnosis of 40 years. To the best of our knowledge, this is the first report of the association of amyloidosis cutis dyschromica and familial mediterranean fever.